2015
DOI: 10.1108/qrfm-04-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral biases of Indian investors: a survey of Delhi-NCR region

Abstract: Purpose – The purpose of this paper is to examine the presence the behavioral biases in Indian investors specifically, overconfidence, excessive optimism (pessimism), herd behavior and the disposition effect. It further investigates the role of demographics and investor sophistication in influencing the biases. Finally, it reveals which bias is most prevalent in the Indian context. Design/methodology/approach – For this purpose, a survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 37 publications
4
83
0
14
Order By: Relevance
“…Although prior studies have significantly contributed to the available literature of behavioral biases and investment decisions (Aren & Aydemir, 2015;Hoffmann et al, 2013;Johnson & Horan, 2013;Prosad et al, 2015). However, this study makes empirical contribution to the existing literature on investor's biases, financial literacy and portfolio diversification.…”
Section: Contribution Of the Studymentioning
confidence: 86%
See 1 more Smart Citation
“…Although prior studies have significantly contributed to the available literature of behavioral biases and investment decisions (Aren & Aydemir, 2015;Hoffmann et al, 2013;Johnson & Horan, 2013;Prosad et al, 2015). However, this study makes empirical contribution to the existing literature on investor's biases, financial literacy and portfolio diversification.…”
Section: Contribution Of the Studymentioning
confidence: 86%
“…Many researchers have focused on financial literacy, behavioral and psychological influence on investor's investment decision (Prosad, Kapoor, & Sengupta, 2015;Hoffmann, Post, & Pennings, 2013;Kumar & Goyal, 2016;Pikulina, Renneboog, & Tobler, 2017). Very few studies have focused on behavior and portfolio diversification (Shinagawa, 2014;Jacobs, Muller, & Weber, 2014;Fuertes, Muradoglu, & Ozturkkal, 2012;Mouna & Anis, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stock market of India has seen many ups and down in recent past. It got to the lowest in 2008 from 2006 and has seen subsequent frequent fluctuations till 2013 [14]. The major financial crisis occurred in 2008 has shaken the world and due to this Investors are restraining themselves to put their hard earned money into the stock market.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only some studies conducted in respect to the Indian market. Some of the important studies that signify the incidence of market wide herding in India in different periods and phases of the stock market are [13,18,19]. Contrastingly, there have been studies that indicate the absence of herding in Indian stock market.…”
Section: Market Wide Herdingmentioning
confidence: 99%
“…The study confirmed strong presence of overconfidence, excessive optimism, disposition and herd behaviour as the major behavioural biases affecting investors' decision. It was also observed that there was significant relationship between demographics, investor characteristics and behavioural biases [18]. An additional eighteen item questionnaire in the Vietnamese version based on the theories of behavioural finance was developed.…”
Section: Qualitative Approachesmentioning
confidence: 99%